Momentum and Reversals When Overconfident Investors Underestimate Their Competition - Luo, Jiang; Subrahmanyam, Avanidhar; Titman, Sheridan (Review of Financial Studies, 2021)
Abstract We develop a model in which overconfident investors overestimate their own signal quality but are skeptical of others’ Investors who are initially uninformed believe that early-informed investors have learned little, leading the former investors to provide excess liquidity, which, in turn, causes underreaction and short-run momentum. Skeptical investors can also react to stale information, causing momentum, followed by reversals. Hence, skepticism generates both momentum and reversals; the latter are amplified if investors overassess their own signal precision. We explain how long-run reversals can disappear while shorter-term momentum prevails, provide empirical implications, and link momentum to liquidity and price efficiency.